AFRICAN AMERICAN VERNACULAR ENGLISH (AAVE) AND THE AMERICAN SOCIETY IN THE 1960’S IN THE HELP NOVEL BY KATHRYN STOCKETT - Nindya Pangestika; Supeno Supeno (Universitas Indraprasta PGRI, 2022)
The aim of this research is to analyze how the African American Vernacular English is applied by the characters and to identify how American society in the 1960’s was portrayed in The Help novel. Using the descriptive qualitative research as a method, this researcher attempts to reveal the characteristics of African American Vernacular English as a language used by the characters in their daily life and American society back in the 1960’s. In identifying the data, theory from Wolfram (2004) about AAVE characteristics and Kurtz (2003) about America’s society in the 1960’s is used. The data were mainly collected from the dialogues of the maids as the native speaker of AAVE.